Effect of Drying Temperature on the Mechanical Properties of Binderless Fiberboard from Bagasse: Study of Flexural and Tensile Strength - Numan Luthfi; Xiulun Wang; Koji Kito; Sunardi Sunardi (JIIF (Jurnal Ilmu dan Inovasi Fisika), 2020)
Sugarcane remains to be one of the largest cash crops in the world. Despite its economic benefits, a large amount of bagasse generated from extraction processing ends up as an environmental issue. The utilization of bagasse as fiberboard is introduced as an alternative waste management. However, nowadays, fiberboard is commonly produced by adding chemical adhesive, such as Urea-formaldehyde resin, which is harmful to living things. The current research was conducted to study and produce environmentally friendly fiberboard by relying only on lignocellulose due to hydrogen bond formation. The methods used consisted of cutting, soaking, refining, concentration determination, and forming with various drying temperatures of 110ºC, 130ºC, 150ºC, 170ºC, and 190ºC. Characterizations of flexural and tensile strength were carried out to investigate the feasibility of fiberboard based on the standard of JIS A 5905 (2003). The calculations show that the increase in drying temperature from 110ºC to 190ºC increased the flexural and tensile fracture stress by 24.12-36.87 MPa and 12.89-19.77 MPa respectively with both maximum values obtained by fiberboard 190ºC. By considering the density and moisture content of fiberboards which ranged from 1.0210-1.0164 g/cm3 and 6.19-4.19% respectively, the results indicate that only fiberboard 110ºC, 130ºC, and 150ºC meet the standard of JIS A 5905 (2003) for high-density fiberboard (HDF) with type of S20 and S25. HDF has applications for exterior siding, interior wall, paneling, and household furniture.